PENGARUH BUDAYA KERJA PEGAWAI NEGERI SIPIL TERHADAP PELAYANAN PUBLIK DI DINAS CATATAN SIPIL DAN KEPENDUDUKAN KOTA PAYAKUMBUH - Frinaldi, Aldri (Humanus, 2014)
The many negative assessments of the work culture of civil servants in public service is an issue that must be addressed by the government and local government. This research was conducted by formulating the problem of how culture influences the work of civil servants in the public service in the Payakumbuh Civil Registry Office in order to analyze the work culture of civil servants in an effort to improve the quality of human resources in public services. This study used a descriptive quantitative approach. The population is all employees in the Payakumbuh’s Department of Population and Civil Registration amounting 30 people based on the data in the month of December 2013. Due to the small number of population in this study, total sampling is applied. The data is collected by spreading questionnaires to all respondents and then returned after some time, whose whole process took place from October to December 2013. The questionnaire was scaled based on Likert scale that is made in a positive statement. The result of the study shows that in general the work culture of civil servants in the Payakumbuh’s Department of Population and Civil Registration are very good, although two indicators are still mediocre. The effort to improve these two indicators are suggested by training programs based on local wisdom and the involvement of stakeholders who are experts in the field by the Payakumbuh administration in building and cultivating a positive work culture based on local wisdom. Keywords: work culture, public servants, public service